Evaluation of Curriculum Implementation of Bachelor of Education Degree in Social Studies in Colleges of Education and Universities of Affiliation in Southwestern Nigeria (2016)
There has been a concern over the non-responsiveness of educational programmes in Nigeria‟s higher institutions to adequately meet social needs. Scholars often lay the blame on poor implementation of curricula, especially social studies. Previous evaluation studies on the products in colleges of education programme showed poor preparation of students without comparing them with their counterparts in the parent universities. This study, therefore, investigated the effectiveness of basic elements of the Social Studies curriculum, the contributions of the Teacher-Related Variables (TRV); qualification, area of specialization, teaching experience, teaching methods, gender and teaching facilities to the Implementation of the Curriculum (IOC) in the Colleges of Education (CoEs) and Universities of Affiliation (UoAs). This is with the view to providing empirical evidence upon which improvement could be made in the preparation of bachelor degree students. The study adopted the descriptive survey design using Stufflebean‟s Context, Input, Process and Product (CIPP) evaluation model. Four colleges of education in Oyo, Osun, Ondo and Lagos states were purposively selected because they run the B.Ed Social Studies on full-time (FT) and part-time (PT) bases. The UoAs and their CoEs are: Ekiti State University – Emmanuel Alayande College of Education, Oyo and Adeniran Ogunsanya College of Education, Lagos. Lagos state University – Osun State College of Education, Ilesha and Obafemi Awolowo University – Adeyemi College of Education, Ondo. Stratified sampling technique was used to select 455 Social Studies students in the CoEs (FT190;PT- 265); UoAs (FT- 110; PT- 120) and their lecturers (CoEs- 47; UoAs - 22). Lecturers‟ Perception of Social Studies Curriculum (r=0.86); Students‟ Perception of Social Studies Curriculum (r=0.74); Teachers Teaching Methods (r=0.70) Social Studies Curriculum Resources (r=0.78) scales, Classroom Teaching Observation Schedule (r=.073) and Social Studies Basic Concepts Test (r=0.78) were used for data collection. Data were analyzed using descriptive statistics, multiple regression and t-test at 0.05 level of significance. The UoAs and CoEs teachers rated the elements of the Social Studies curriculum to be effective with mean scores ( ̅ = 3.02 and ̅ = 2.80) respectively. Students‟ ratings of the elements of Social Studies curriculum in the UoAs ( ̅ = 3.25) and CoEs ( ̅ = 2.96) were effective. For the UoAs resource input availability ( ̅= 1.82) and adequacy ( ̅= 1.81) were obtained in the UoAs while CoEs had ̅=1.72 and ̅ = 1.73 respectively. The TRV and teaching facilities had significant composite contribution to IOC in the UoAs, (F(6,26) = 3.23: R2 = 0.39) and CoEs, (F(6,45) = 3.92:R2 = 0.26) with 39% and 26% respective contributions to the variance of IOC. Teaching experience (β=.08,t= .37) and qualification (β = -.52, t = .2.16) made significant relative contributions to the IOC in the UoAs, while area of specialization (β = -.29, t = 2.05) and teaching facilities (β=.25,t=1.81) contributed significantly in the CoEs. The implementation of bachelor of education degree in Social Studies curriculum was more effective in the universities than colleges of education. There should be provision of adequate facilities for the colleges of education to improve on the implementation of their curricula